Fish By-Products Utilization in Food and Health: Extraction Technologies, Bioactive, and Sustainability Challenges - Waqar M; Sajjad N; Ullah Q; Vasanthkumar SS; Ahmed F; Panpipat W; Aluko RE; Kaur L; Chaijan M; Ageru TA (Wiley Periodicals LLC, 2025)
Fish by-products, traditionally regarded as waste, are increasingly recognized as valuable sources of bioactive compounds, including peptides, omega-3 fatty acids, collagen, and hydroxyapatite. These molecules exhibit significant functional properties with applications in food preservation, dietary supplementation, pharmaceuticals, and cosmeceuticals. This review explores advanced extraction technologies such as enzyme-assisted hydrolysis, supercritical fluid extraction, and cold plasma processing, which enhance the yield and stability of bioactives while supporting zero-waste and circular economy principles. Despite technological progress, key barriers remain, including inconsistent raw material quality, high processing costs, regulatory uncertainty, and limited industrial infrastructure. Peptides and protein hydrolysates derived from fish frames, skins, viscera, and scales have demonstrated antioxidant, antihypertensive, antimicrobial, antidiabetic activities, but translation into functional food and health products is constrained by scalability and regulatory challenges. Future work should focus on optimizing bioprocessing, validating health benefits through clinical trials, and implementing sustainable valorization frameworks. Addressing these challenges will unlock the full potential of fish by-products in advancing food security and human health.
Keywords: bioactive peptides; circular economy; fish by-products; functional foods; health applications; sustainable extraction